2018
DOI: 10.1142/s0129054118400014
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Palindromic Factorization is NP-Complete

Abstract: We prove that it is NP-complete to decide whether a given string can be factored into palindromes that are each unique in the factorization.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…A substring S[i..j] is called a palindromic substring of S if S[i..j] and the reversed string of S[i..j] is the same string. The study of combinatorial properties and structures on palindromes is still an important and well studied topic in stringology [1,3,4,5,8,14]. Droubay et al [3] showed a string of length n can contain at most n + 1 distinct palindromes.…”
Section: Introductionmentioning
confidence: 99%
“…A substring S[i..j] is called a palindromic substring of S if S[i..j] and the reversed string of S[i..j] is the same string. The study of combinatorial properties and structures on palindromes is still an important and well studied topic in stringology [1,3,4,5,8,14]. Droubay et al [3] showed a string of length n can contain at most n + 1 distinct palindromes.…”
Section: Introductionmentioning
confidence: 99%
“…To derive our result we consider a specific factorization of a rich word into distinct rich palindromes, here called UPS-factorization (Unioccurrent Palindromic Suffix factorization), see Definition 3.2. Let us mention that another palindromic factorizations have already been studied, see [3,7]: Minimal (minimal number of palindromes), maximal (every palindrome cannot be extended on the given position) and diverse (all palindromes are distinct). Note that only the minimal palindromic factorization has to exist for every word.…”
Section: Introductionmentioning
confidence: 99%